An audit of thyroidectomy for Graves' Disease, in a large UK tertiary centre. (1st March 2022) - Jones, Larissa; Khan, Shaila; Tolley, Neil; Palazzo, Fausto; Cox, Jeremy; Agha-Jaffar, Rochan; Robinson, Stephen; Di Marco, Aimee
Abstract: Aims: Patients undergoing thyroidectomy for Graves' disease are at increased risk of post-operative complications and therefore require additional pre-operative preparation and close post-operative assessment. This study aimed to assess the pre- and post-operative management and morbidity in a single UK tertiary centre. Method: Retrospective analysis of patients undergoing thyroidectomy for Graves' between 2014–19. The primary endpoint was thyroid status pre-operatively and post-operative morbidity. Secondary endpoints were administration of potassium iodide, vitamin D and beta blockers and assessment of post-operative parathyroid function. Results: Ninety-two thyroidectomies were undertaken for Graves' in the five-year period. Pre-operatively 98% were successfully rendered euthyroid or hypothyroid and 2% hyperthyroid but required emergency surgery. Post-operative hypocalcaemia occurred in 26% but was temporary in 92%. Vocal cord palsy was found in 11%, but in all cases was temporary (post-operative laryngoscopy was reported in 93%). 49% had received potassium iodide, 53% beta-blockers and 48% vitamin D. Post-operative calcium and PTH estimation was undertaken on day 0 in 99% and 97% respectively and day 1 in 100% and 98%. Conclusion: This audit of specialist practice shows a majority of patients rendered eu- or hypothyroid pre-operatively and low complication rates, with the majority being temporary. Pre-operative medical optimization was not undertaken uniformly in all patients and although outcomes were good, a protocol to improve consistency has been developed in response.